Structure peculiarities of visual caused potentials of female athletes with individual profile of asymmetry - Mendzheritskiy, A. M.; Aydarkina, M. E.; Karantysh, G. V.; Dmitrenko, L. M. (The Russian Journal of Physical Education and Sport, 2016)
Annotation. In recent years the theory of functional asymmetry of brain cortex is actively developed. Also the influence of sensomotor features formation on compensatory-adaptive mechanisms of brain during the process of ontogenesis and in terms of different factors influence on an organism is studied. In this connection especially interesting is the study of an individual profile of asymmetry and visual-motor coordination of sportsmen-beginners. Material. The article presents the results of a comparative analysis of visual caused potentials among female athletes and girls, who don`t go in for sport with different lateral phenotype (ambidexters according to a hand and an eye and ambidexters according to a hand and preference of the left eye). Research methods: scientific literature analysis and summarizing, experiment,neurophysiological examination, testing, cross-correlation analysis. Result. On the basis of the received results of latencies and amplitude indices of a caused bioelectric brain activity a cross-correlation analysis was held. It is stated, that in the control groups of girls the structure of visual caused potentials is better formed among ambidexters with the preference of the left eye in comparison with the ambidexters according to an eye. In a group of young female athletes caused potentials are better formed among those, who have preference according to a hand and an eye and who also have more innerhemispheric connections between occipital and other parts of a brain and greater number of correlational connections between bioelectric processes in vertex and other parts of a brain.